E-047 Staged approach to complex Y-stenting for wide-necked bifurcation aneurysms. (23rd July 2022) - Hindi, M; Elmoursi, S; Dornbos, D; Pahwa, S; Sheikhi, L; Fraser, J
Abstract : Purpose: The treatment of wide-necked bifurcation aneurysms (WNBA) is evolving rapidly. Complex techniques, such as Y-stent-assisted coiling (Y-SAC), in which coils are deployed over a dual-stent assembly, with one passing through the interstices of the other, are effective but present unique challenges and complications. We describe the results of a staged Y-SAC method for unruptured WNBAs. Methods: We retrospectively reviewed the records of patients harboring WNBAs treated at our institution with staged Y-SAC between 2015 and 2021. Inclusion criteria were adult patients with unruptured intracranial bifurcation aneurysms with wide necks, defined as neck width ≥ 4 mm or a dome/neck ratio ≤ 2. Primary endpoint was periprocedural risk of staged Y-SAC, defined by major complications (ischemia or hemorrhage within 48 hours of the procedure) or minor complications (pharmacologic or other complications requiring intervention). Secondary endpoints were degree of initial and follow-up occlusion, characterized by Raymond-Roy (RR) class, as well as need for retreatment. These outcomes were qualitatively compared with data in extant Y-SAC studies. Results: A total of 21 patients (13 female, mean age 61.1) underwent successful staged Y-SAC for unruptured WNBAs (eight anterior communicating, six middle cerebral, six basilar tip, one internal carotid artery terminus). Mean dome/neck ratio was 1.55. Mean interval between stages was 52.1 days. Major complications occurred in one (4.76%) patient who had a non-occlusive thrombus near their stent on postoperative day two after trauma. There were no intraoperative or interoperative ruptures or other hemorrhagic complications. Minor complications included two (9.52%) asymptomatic intraoperative thromboses treated effectively with GpIIb/IIIa inhibitors and one (4.76%) intraoperative access site complication requiring vascular consult. Immediately following the second stage, eight (38.1%) cases had complete occlusion, with five (23.8%) neck remnants, and eight (38.1%) aneurysm remnants. Follow-up angiography was available for 15 patients (mean follow-up of 6.01 months) and revealed complete occlusion in 12 (80%), neck remnant in one (6.67%), and aneurysm remnants in two (13.3%). Adequate occlusion (RR1 or RR2) was achieved in 86.7% of cases. Two (9.52%) aneurysms required retreatment over one year after initial treatment. Compared to recent Y-SAC series, which reported rates of ischemia or hemorrhage from 0% ( n = 15) to 16.7% ( n = 6), our cohort demonstrates low (1 subject; 4.76%) rates of major complications. Furthermore, that patient presented after trauma postoperatively, which may have played a role in this complication. Operative outcomes are comparable with current literature, which report long-term adequate occlusion ranging from 80% ( n = 15) to 100% ( n = 18), compared to 86.7% in the present study. Angiographic follow-up is not yet available in three of our patients, and three others were lost to follow-up or died of unrelated causes. Conclusion: In this cohort, we find that staged Y-SAC is safe and effective in the treatment of unruptured WNBAs, demonstrating low rates of major complications and favorable rates of long-term occlusion. Most notably, the absence of any ruptures or hemorrhagic complications demonstrates that a staged approach may increase the feasibility of Y-SAC by providing a more stable construct through which treatment is completed. Disclosures: M. Hindi: None. S. Elmoursi: None. D. Dornbos: None. S. Pahwa: None. L. Sheikhi: None. J. Fraser: None.